Mesenchymal stem cells suppress hepatic fibrosis accompanied by expanded intrahepatic natural killer cells in rat fibrosis model - UĞURLU, MUSTAFA ÜMİT; AKKOÇ, TUNÇ (SPRINGER, 2019)
Natural killer (NK) cells have antifibrotic effects. We have evaluated the influence of rat bone marrow-mesenchymal stem cell (BM-MSC) treatment on liver histology, biochemical liver function tests, systemic immunoregulatory state and NK cell distribution in liver and peripheral blood in rat model of common bile duct (CBD) ligation and compared the results with the control group. Rats were divided into three groups: (1) CBD ligated (CBDL) rats received phosphate-buffered saline (CBDL+PBS group) or (2) MSC (CBDL+MSC group) and sham-operated rats received MSC (healthy+MSC group). We found significantly decreased fibrosis scores with BM-MSC treatment in CBDL rats compared to the control (CBDL+PBS) group while no fibrosis developed in sham operated (healthy+MSC) group. BM-MSC treatment has decreased the inflammation as reflected by the significantly decreased T cell proliferation and inflammatory cytokine concentrations from splenocyte culture and liver tissue itself compared to CBDL+PBS. NK cells both in parenchyme and portal areas decreased significantly in liver and blood in CBDL+PBS compared to healthy+MSC while they were found to be increased in CBDL+MSC compared to CBDL+PBS rats. In conclusion, BM-MSCs may suppress hepatic fibrosis accompanied by expanded intrahepatic NK cells in CBDL rats. Thus, our animal study shows that MSC treatment holds great promise for treatment of patients with end-stage liver diseases through a possible mechanism by adopting the NK cell population and new studies investigating the role of NK cells and clinical fibrosis are warranted.Trial registration number: Marmara University Animal Care and Use Committee approval code: 73.2013.mar.
Keywords: Cell therapy; Stem cells; Animal models; Natural killer cells; NK CELLS; LIVER; INFLAMMATION; INFUSION